Reflection on the role and design of specialised translation dictionaries - Tarp, Sven (MonTi Monografías de Traducción e Interpretación, 2015)
This article deals with specialised translation dictionaries. Based on the principles of the function theory, it analyses the different phases and sub-phases of the translation process from a lexicographical perspective and shows that a translation dictionary should be much more than a mere bilingual dictionary if it really aims to meet its users’ complex needs. Thereafter, it presents a global concept of a translation dictionary which includes various mono- and bilingual components in both language directions. Finally, the article discusses how this concept can be applied on the Internet in order to develop high-quality translation dictionaries with quick access to data that are still more adapted to the needs of each translator.